The Essential Thrombocythemia, Thrombotic Risk Stratification, and Cardiovascular Risk Factors - Salvatrice Mancuso; Vincenzo Accurso; Marco Santoro; Simona Raso; Angelo Davide Contrino; Alessandro Perez; Florinda Di Piazza; Ada Maria Florena; Antonio Russo; Sergio Siragusa (Advances in Hematology)
Essential thrombocythemia is a rare hematological malignancy with good overall survival, but moderate to high risk of developing arterial or venous thrombosis lifelong. Different thrombotic risk scores for patients with essential thrombocythemia have been proposed, but only one of them (the IPSET-t scoring system) takes into account the classical cardiovascular risk factors as one of the scoring items. Currently, in clinical practice, the presence of cardiovascular risk factors in patients with diagnosis of ET rarely determines the decision to initiate cytoreductive therapies. In our study, we compared different risk models to estimate the thrombotic risk of 233 ET patients and the role of specific driver mutations and evaluated the impact that conventional cardiovascular risk factors (hypertension, cigarette smoking, diabetes, obesity, and dyslipidaemia) have on thrombotic risk in patients with ET. Perspective studies conducted on a polycentric large cohort of patients should be conducted to estimate the impact of cardiovascular risk factors in determining thrombosis in ET patients, evaluating the opportunity of initiating a cytoreductive therapy in patients with cardiovascular risk factors, even if classified into low to moderate risk groups according to other scoring systems.